EFFECT OF ESSENTIAL OILS ON BIOFILM FORMATION BY PROTEUS MIRABILIS - MATHUR S.; UDGIRE M.; KHAMBHAPATI A. (International Journal of Pharma and Bio Sciences, 2013)
There is an increasing evidence of antibiotic resistance due to the formation of bacterial biofilm in various wounds and urinary tract infections (UTIs). Biofilm formation by Proteus mirabilis on urinary catheter has posed to be a great risk and further complicates the infection. The aim of the present study was to evaluate the effect of five essential oils, as, Garlic, Eucalyptus, Neem, Tulsi, and Clove, on the biofilm formation by Proteus mirabilis MTCC 425 strain. Out of all the five essential oils, Eucalyptus oil showed highest marked reduction in the biofilm formation by P. mirabilis MTCC 425. This was followed by a slight reduction in biofilm formation by Garlic, Tulsi, Neem and Clove oil. The Eucalyptus oil showed the maximum reduction in biofilm formation; hence it was used to check the inhibition effect on biofilm formation on catheter. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the Eucalyptus oil against the P. mirabilis strain was also found out and the MIC was found out to be 300μl/ml and MBC to be 1200μl/ml